The legal system for delay fine in administrative contract According to modern judicial applications of the Council of the Syrian state - Al halak, Muhammad; Aljamae, Hussam (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Law No.(51) for year of 2004 related with contract systems of public entities in Syria includes confirmations of execution of administrative contracts, which did not aim basically for obliging the contractor to execute agreed contracting provisions only, as achieving the right execution of necessary commitment for working of public utility without stopping or fault. The most important of these confirmations is delay fine, which considered the most important financial penalty which the administration owns towards the contractor with it, who delay in execution of its contracting obligations, in addition to the objective of stimulating the contractor to execute its commitments according to defined periods and provisions which agreed upon in contract items, therefore, imposing delay fine will be considered as compensation of administration for the damage which represented in stop of public utility, if it is allowed for the contractor to default or delay for execution of its commitments without sanction, this will be a reason for breakdown of public utility and loss of public interest, for preventing this, delay fine appeared in range of execution of administrative contracts, which lead to many problems which result by modern practical applications in the Council of the Syrian State for imposing it and how to calculate and divide it, in addition to justification of delay of contractor in execution of its commitments temporally, and cases of exempting him from delay fine finally. النظام القانوني لغرامة التأخير في العقد الإداري وفق التطبيقات القضائية الحديثة لمجلس الدولة السوري يتضمن القانون رقم (51) لعام 2004 الخاص بنظام العقود للجهات العامة في سوريا مؤيدات تنفيذ العقود الإدارية، تلك المؤيدات التي لا تهدف في الأساس إلى إلزام المتعاقد بتنفيذ الشروط التعاقدية المتفق عليها فحسب بقدر ما تتغيّا تحقيق التنفيذ السليم للالتزام الضروري لسير المرفق العام دون توقف أو تعطيل، وأهم تلك المؤيدات هي غرامة التأخير التي تُعدُّ من أهم الجزاءات المالية التي تملكها الإدارة في مواجهة المتعاقد معها في حال تقصيره أو تأخره في تنفيذ التزاماته التعاقدية، إضافةً لغايتها في حث المتعاقد على تنفيذ التزاماته وفق الشروط والمدد الزمنية المُحددة والمُتفق عليها في بنود العقد، بحيث إن توقيع غرامة التأخير يُعدُّ بمثابة تعويض للإدارة عن الضرر المتمثل بتعطيل سير المرفق العام؛ فلو تُرك الأمر مفتوحاً أمام هذا المُتعاقد لتقصيره أو تأخُّره عن تنفيذ التزاماته دون رادع، لكان ذلك سبباً لتعطيل حسن سير المرافق العامة وضياع المصلحة العامة، ومنعاً لذلك ظهرت غرامة التأخير في نطاق تنفيذ العقود الإدارية، والتي يثور معها العديد من المشكلات التي أفرزتها التطبيقات العملية الحديثة لدى مجلس الدولة السوري لجهة فرضها وكيفية حسابها و تجزئتها، إضافةً لتبرير تأخُّر المتعاقد في تنفيذ التزاماته بشكل مؤقت، و حالات إعفائه من غرامة التأخير بشكل نهائي.